2003
DOI: 10.1038/sj.npp.1300202
|View full text |Cite
|
Sign up to set email alerts
|

Psychoactive Drugs and Pilot Performance: A Comparison of Nicotine, Donepezil, and Alcohol Effects

Abstract: The cholinergic system plays a major role in cognitive abilities that are essential to piloting an aircraft: attention, learning, and memory. In previous studies, drugs that enhance the cholinergic system through different pharmacologic mechanisms have shown beneficial effects on cognition; but dissimilar cognitive measures were used and samples were not comparable. A comparison within the same cognitive tasks, within comparable samples appears desirable. Toward this aim, we compared effect sizes (ES) of perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 35 publications
1
26
1
1
Order By: Relevance
“…One study which investigated the effect of a single dose of transdermal nicotine in nonsmokers, with attention as the primary outcome, described improvement in performance on the Conners' CPT as reflected by a reduction in hit reaction time variability and omission errors, however, no medication effect was seen on commission errors (Levin et al, 1998). Our results with a different CPT and a higher dose of nicotine, are consistent although not identical with these results and provide further evidence that nicotinic receptor stimulation leads to cognitive benefits in individuals without cognitive impairment (Le Houezec et al, 1994;Foulds et al, 1996;Levin et al, 1998;Mumenthaler et al, 2003).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…One study which investigated the effect of a single dose of transdermal nicotine in nonsmokers, with attention as the primary outcome, described improvement in performance on the Conners' CPT as reflected by a reduction in hit reaction time variability and omission errors, however, no medication effect was seen on commission errors (Levin et al, 1998). Our results with a different CPT and a higher dose of nicotine, are consistent although not identical with these results and provide further evidence that nicotinic receptor stimulation leads to cognitive benefits in individuals without cognitive impairment (Le Houezec et al, 1994;Foulds et al, 1996;Levin et al, 1998;Mumenthaler et al, 2003).…”
Section: Discussionsupporting
confidence: 66%
“…Previous studies investigating the effects of nicotine on attention in nonsmokers without psychiatric disorder have yielded inconsistent findings (Heishman et al, 1993;Le Houezec et al, 1994;Foulds et al, 1996;Levin et al, 1998;Heishman and Henningfield, 2000;Ernst et al, 2001;Mumenthaler et al, 2003;Sacco et al, 2004). Although it has been suggested that individuals with optimal baseline performance may experience deterioration in performance with nAChR stimulation unless task demands are very high (Newhouse et al, 2004), variation in findings may also be attributed to differences in the measure used to assess attentional performance or, as above, to pharmacological differences such as dose or mode of administration of nicotine.…”
Section: Discussionmentioning
confidence: 99%
“…In related work (Sahakian et al 1993) they show that the cholinesterase inhibitor tetrahydroaminoacradine improves AD patients' release latency and movement time in an analog of our RT procedure without affecting performance on analogs of our DMS and vsPAL procedures. Interestingly while some studies in human volunteers report improved sustained attention with nicotine (Mumenthaler et al 2003), others report improved memory performance in the absence of attentional improvement (Howe and Price 2001;Min et al 2001). Similar to this latter work, nicotine failed to significantly improve the battery measures which are most consistent with vigilance and sustained attention, namely release latency in the RT procedure and the time of last response in the PR procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Sun et al (1999) reported improved memory and learning functions in adolescent Chinese students following a 4-week administration of an AChE-I (huperzine-A). Recent studies in healthy aircraft pilots reported beneficial effects on the retention of complex tasks (flight simulator) after 30 days of donepezil treatment (Yesavage et al 2002;Mumenthaler et al 2003). However, the tasks were very complex and tapped a combination of cognitive functions that were difficult to distinguish.…”
Section: Introductionmentioning
confidence: 99%